Kecenderungan Politik Internasional Kontemporer - Arfani, Riza Noer (Jurnal Ilmu Sosial dan Ilmu Politik, 1999)
Trends in contemporary international polities in the post-cold war era should be observed and learned in the following phenomena: urupolansm of military and political forces under US hegemony, and mulupolansm in international economic forces. The relatively novel sacra-cultural values of the so-called pragmatr-sm and economism are proliferating in response to and alongside with the most recent development of world capitalism. At the same time, actors in the international arena multiplies as the need to solve and manage various problems and issues crosses over the mandate and legitimacy of the state Ã¢â¬â long considered as the dominant actor in international politics.Agenda to be developed by nations should as well examine and look at carefully issues and problems generated by those aforementioned trends at the international arena. This is to underline the need to not overemphasizing high profile foreign policies, while at the same time neglecting the so-called kw-politics issues. Developing nations in parricularare among the first group to be concerned with as they mostly do not have adequate space to play with in -what Dudley Seers called asÃ¢â¬â their `morn to ma.noezi we. That is the mom to being independent in taking steps, formulating policies, and maneuvering in (or resisting against) the globalized market forces